2006
DOI: 10.1007/s00213-006-0630-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of reward processes in an animal model of depression

Abstract: Rationale Anhedonia is a core symptom of major depression. Deficits in reward function, which underlie anhedonia, can be readily assessed in animals. Therefore, anhedonia may serve as an endophenotype for understanding the neural circuitry and molecular pathways underlying depression.Objective Surprisingly, there is scant knowledge regarding alterations in brain reward function after olfactory bulbectomy (OB), an animal model which results in a behavioural syndrome responsive to chronic antidepressant treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(65 citation statements)
references
References 57 publications
3
61
0
1
Order By: Relevance
“…Furthermore, in rats, CMS induces an increased immobility in the FST associated with a decrease in reward sensitivity as measured by increased intracranial self-stimulation threshold, attenuated sucrose consumption, decreased preference for alcohol, impaired sexual behaviour and decreased amphetamine and morphine rewarding effects (Willner 2005). Similarly, olfactory bulbectomy that exhibits a high degree of neurochemical similarity to depression induces a decreased sensitivity to reward as shown by a decreased sexual behaviour (Lumia et al 1992), an increased intracranial self-stimulation threshold (Slattery et al 2007) and a reduced cocaine place preference (Calcagnetti et al 1996).…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, in rats, CMS induces an increased immobility in the FST associated with a decrease in reward sensitivity as measured by increased intracranial self-stimulation threshold, attenuated sucrose consumption, decreased preference for alcohol, impaired sexual behaviour and decreased amphetamine and morphine rewarding effects (Willner 2005). Similarly, olfactory bulbectomy that exhibits a high degree of neurochemical similarity to depression induces a decreased sensitivity to reward as shown by a decreased sexual behaviour (Lumia et al 1992), an increased intracranial self-stimulation threshold (Slattery et al 2007) and a reduced cocaine place preference (Calcagnetti et al 1996).…”
Section: Discussionmentioning
confidence: 97%
“…Conversely, the NMDA antagonist ketamine, which primarily 902 depresses ICSS in the absence of explicit stress, also failed to reverse depression of ICSS induced by socialdefeat stress in mice (Donahue et al, 2014). Other research has shown that repeated stress can enhance amphetamine-induced facilitation of ICSS (Lin et al, 2002), whereas effects of cocaine and THC were not altered by olfactory bulbectomy or repeated stress, respectively (Slattery et al, 2007;Fokos and Panagis, 2010). Together, these results illustrate the potential for differential effects of stress as a modulator of abuserelated drug effects in ICSS procedures, but given the prominent role of stress as a risk factor in drug abuse (Neisewander et al, 2012;Volkow et al, 2012), this is a relatively undeveloped theme of research.…”
Section: A Statesmentioning
confidence: 89%
“…Brain reward systems, including the mesolimbic DA system, have been implicated in mood disorders (Nestler and Carlezon, 2006;Russo and Nestler, 2013), and ICSS has been used in preclinical studies aimed at identifying determinants of stress-related depression of positively reinforced behavior. Regimens of repeated stress, including chronic, intermittent exposure to stressors like restraint and soiled bedding (Moreau et al, 1992(Moreau et al, , 1994 or social defeat (Donahue et al, 2014), have been reported to depress basal ICSS, and ICSS was also depressed by an olfactory bulbectomy model of depression (Slattery et al, 2007). However, other regimens of chronic stress had no effect on ICSS (Fokos and Panagis, 2010) or produced effects that varied across time or across test subjects (Nielsen et al, 2000;Lin et al, 2002).…”
Section: A Statesmentioning
confidence: 99%
“…The sucrose preference test (Willner, 1997), intra-cranial self-stimulation (Slattery et al, 2007), and operant tests such as sucrose pellet reinforcement on a progressive ratio schedule (Ineichen et al, 2012), are examples of relevant readout tests.…”
Section: Discussionmentioning
confidence: 99%